Ketenagakerjaan Dalam Perspektif Omnibus Law - Anggreany Haryani Putri (KRTHA BHAYANGKARA, 2021)
Omnibus Law is a new legal product designed as a form of breakthrough to replace existing regulations or laws. This is inseparable from the advantages possessed by the omnibus law itself. As a regulation that contains more than one regulatory content, Omnibus Law is able to overcome overlapping regulations. the application of the Omnibus law can simplify regulations by revoking or amending a number of laws that have been in effect previously. In the Job Creation Bill, employment is one of the clusters discussed, Apart from the lack of compliance with the current situation and developments in the Manpower Act, Indonesia is also still faced with other problems in the form of a less conducive labor climate, investment and business climate and not yet optimal creation. employment in the country. Through the Omnibus Law, the government will make improvements to the substance of Law no. 13 of 2003 concerning Labor that is more equitable and supports the investment climate by continuing to improve the protection and welfare of workers by regulating the fulfillment of the constitutional rights of article 27 paragraph 2 of the 1945 Constitution of the Republic of Indonesia by regulating Foreign Workers, Outsourcing, Termination of Employment, Working Hours, and minimum wages.